2012
DOI: 10.1074/jbc.m112.425652
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Timp3 Gene Leads to Abdominal Aortic Aneurysm Formation in Response to Angiotensin II

Abstract: Background: TIMP3 is ECM-bound and is implicated in patients with abdominal aortic aneurysm (AAA). Results: Timp3 deficiency triggers AAA in response to Ang II. Additional deletion of Mmp2 exacerbated AAA with enhanced inflammation. Broad spectrum MMP inhibition prevented AAA in both genotypes. Conclusion: TIMP3 is protective against Ang II-mediated adverse remodeling. Significance: Replenishment of TIMP3 in aneurysmal aorta could prevent aneurysm expansion and rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 66 publications
(72 reference statements)
2
55
0
Order By: Relevance
“…This result is consistent with those of previous studies showing that MMP-2 expression is regulated by Hif-1α. The expression of tissue inhibitors of metalloproteinase-3, which suppresses activity of MMPs, 10 was unchanged in both groups ( Figure IX in the online-only Data Supplement). In addition, there was no difference in the expression of inflammation-related genes between the groups after 6 weeks.…”
Section: Discussionmentioning
confidence: 87%
“…This result is consistent with those of previous studies showing that MMP-2 expression is regulated by Hif-1α. The expression of tissue inhibitors of metalloproteinase-3, which suppresses activity of MMPs, 10 was unchanged in both groups ( Figure IX in the online-only Data Supplement). In addition, there was no difference in the expression of inflammation-related genes between the groups after 6 weeks.…”
Section: Discussionmentioning
confidence: 87%
“…Ang II-mediated AAA formation in ApoE -/-and LDLR -/-mice was independent of the blood pressure as suppression of hypertension (by hydralazin administration) did not prevent AAA or atheroscrlerosis in these mice [51]. Recently, we reported that despite the suppressed Ang II-induced hypertension in TIMP3 -/-mice, these mice develop AAA after 4 weeks of Ang II infusion while WT mice did not [48]. Overall, sufficient evidence indicate ECM degradation and as the central and initiating event in development of AAA, while comorbidities such as atherosclerosis and hypertension may or may not be present with AAA.…”
Section: Aortic Aneurysm Occurs Independently From Hypertension and Amentioning
confidence: 99%
“…-/-mice with a hypertensive dose of Ang II resulted in a suppressed hypertensive response [76], but development of AAA after 4 weeks of Ang II infusion, whereas wildtype mice, that had increased TIMP3 levels in the abdominal aorta, did not exhibit AAA [48], suggesting a protective function of TIMP3 in this process ( Figure 1). Although elevated MMP2 activation was detected in the abdominal aorta after 2 weeks of Ang II infusion, ablation of MMP2 in TIMP3 -/-mice exacerbated AAA dilation and increased the rate of aortic rupture, primarily due to heightened inflammation.…”
Section: Infusion Of Timp3mentioning
confidence: 99%
See 2 more Smart Citations